Two‐Dimensional Tetrathiafulvalene Covalent Organic Frameworks: Towards Latticed Conductive Organic Salts. Issue 45 (29th April 2014) - Jin, Shangbin; Sakurai, Tsuneaki; Kowalczyk, Tim; Dalapati, Sasanka; Xu, Fei; Wei, Hao; Chen, Xiong; Gao, Jia; Seki, Shu; Irle, Stephan; Jiang, Donglin
Abstract The construction of a new class of covalent TTF lattice by integrating TTF units into two‐dimensional covalent organic frameworks (2D COFs) is reported. We explored a general strategy based on the C2+C2 topological diagram and applied to the synthesis of microporous and mesoporous TTF COFs. Structural resolutions revealed that both COFs consist of layered lattices with periodic TTF columns and tetragonal open nanochannels. The TTF columns offer predesigned pathways for high‐rate hole transport, predominate the HOMO and LUMO levels of the COFs, and are redox active to form organic salts that exhibit enhanced electric conductivity by several orders of magnitude. On the other hand, the linkers between the TTF units play a vital role in determining the carrier mobility and conductivity through the perturbation of 2D sheet conformation and interlayer distance. These results open a way towards designing a new type of TTF materials with stable and predesignable lattice structures for functional exploration.